Upaya Meningkatkan Hasil Belajar Lompat Jauh Gaya Jongkok Melalui Penggunaan Media Alat Bantu Box bagi Siswa SDN 38 Ampenan - Magdalena, Magdalena (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
This study aims to improve learning outcomes squat-style long jump through the use of the media as a tool for students at SD Negeri 38 Ampenan. This research method uses classroom action research methods with research subjects namely fifth grade students of SD Negeri 38 Ampenan. The research instrument used observation, interviews, and tests. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that learning the long jump squat style through the use of assistive media can increase student focus and activeness as well as a pleasant learning atmosphere which has an impact on improving student learning outcomes.